Consumer behaviour in online shopping - An empirical study on consumer online shopping behaviour - Vaghani, Rahi (2012)
This dissertation focuses on customer deeds in the online shopping environment. It seeks answers to three main questions: 1. What are the criteria dimensions of observed chance in the online shopping environment? 2. Will customers behave contrarily for services and goods in the online shopping environment? 3. What are the antecedents of consumers’ online buying intention? A survey of continuing customer online shopping deeds works and relevant marketing and data arrangements works is led to craft the hypothetical and conceptual foundation for this study. Instituted on the survey, scrutiny models and scrutiny hypotheses are formulated and industrialized for consecutive empirical testing. Experiential surveys are retained to examination of the scrutiny hypotheses. The main findings of this dissertation are: